(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of patients with Klebsiella pneumoniae bacteremia treated in the Department of Infectious Diseases, Hai Duong General Hospital, from January 1, 2023 to September 30, 2025. Subjects and Methods: A descriptive cross-sectional study was conducted in 31 patients diagnosed with Klebsiella pneumoniae bacteremia. Results: The mean age was 66.0 ± 15.98 years; patients older than 60 years accounted for 67.7%; males comprised 58.1%. Overall, 70.1% had comorbidities, most commonly cardiovascular diseases and diabetes mellitus (both 35.5%); cirrhosis accounted for 9.4% and chronic gout for 6.5%. The most common portals of entry were the respiratory and gastrointestinal tracts (19.4%). A total of 54.9% of patients were admitted within 1–3 days from symptom onset. Severe cases transferred to a higher-level hospital accounted for 6.5%, and 3.2% of severe patients were discharged against medical advice. The mean length of hospital stay was 15.16 ± 6.9 days. Fever occurred in 90.3% of patients, commonly moderate to high fever (70.9%), intermittent fever (87.1%), and chills/rigors (16.1%). No patients developed shock or respiratory failure. Mean arterial pressure was 88.5 ± 14.68 mmHg, and mean heart rate was 93.9 ± 15.3 beats/min. The mean white blood cell count was 10.6 ± 6.2 G/L; 66.7% had neutrophilia (neutrophils > 75%). Mean CRP was 100.6 ± 65.7 mg/L, with 60% having CRP > 100 mg/L. Mean procalcitonin was 16.7 ± 25.4 ng/mL, and 40% had procalcitonin > 10 ng/mL. The proportion of liver abscess was 8.3%. Conclusion: Klebsiella pneumoniae bacteremia is common in older adults, particularly males and those with underlying comorbidities, with fever and elevated inflammatory markers being the most frequent clinical manifestations.